Sleep as a mediator of the relationship between social class and health in higher education students - McGuffog, R.; Rubin, M.; Boyes, Mark; Caltabiano, M.L.; Collison, J.; Lovell, G.P.; Muldoon, O.; Paolini, S. (2023)
A substantial body of research indicates that higher education students from lower social class backgrounds tend to have poorer health than those from higher social class backgrounds. To investigate sleep as a potential mediator of this relationship, online survey responses of students from five large Australian universities, one Irish university and one large Australian technical college were analysed in three studies (Study 1 N = 628; Study 2 N = 376; Study 3 N = 446). The results revealed that sleep quality, sleep duration, sleep disturbances, pre-sleep worries and sleep schedule variability mediated the relationship between social class and physical and mental health. Sleep remained a significant mediator when controlling for related variables and other mediators. Thus, the findings suggest that sleep partly explains social class differences in health. We discuss the importance of addressing sleep issues among students from lower social class backgrounds.